Impact of cattle grazing on temperate coastal salt marsh soils - Di Bella, Carla Estefania; Rodríguez, Adriana Mabel; Jacobo, Elizabeth Juliana; Golluscio, Rodolfo Angel; Taboada, Miguel Angel (Wiley, 2019)
Over the last two decades, grazing intensity has increased in the temperate salt marshes of Samborombón Bay (Argentina) due to agricultural expansion and the displacement of domestic livestock to these areas. We investigated the effect of cattle grazing on soil chemical and physical properties in the higher (HE), medium (ME) and lower (LE) elevation levels of this temperate salt marsh. Soil data were collected from both a National Park, where cattle grazing has been excluded for more than 35 yrs, and an adjacent commercial livestock farm continuously grazed by cattle. We found that soil salinity was greater on the grazed than on the ungrazed sites, especially those in the ME and LE. This could be related to the upward flow of salts from the saline groundwater, driven by the increase in the proportion of bare soil on grazed sites. The increase in soil salinity changed the plant community structure through the increase of salt‐tolerant and non‐palatable species and the decrease of palatable species. Soil physical variables (soil bulk density and soil bearing capacity) were also higher on the grazed than on the ungrazed sites, which can be related to the decrease in soil organic matter (SOM), and suggest an incipient compaction process; however, the values were still lower than those considered critical for plant growth in clay soils. These results suggest that continuous grazing management in this temperate salt marsh might have negative consequences for animal production and ecosystem conservation, mainly related to the increased soil salinity. Further research will be necessary to evaluate the suitability of switching to intermittent grazing management.